1991
DOI: 10.1107/s0108768191001672
|View full text |Cite
|
Sign up to set email alerts
|

Pb2+ cation ordering in Pb3(Mo4O6)4

Abstract: help in selecting and mounting the crystals, and to Dr P. Piret for sending us a preprint of his work. We are also grateful to Professor D. E. Appleman for his suggestions. ReferencesBIANCm, R., PILATI, T., DIELLA, V., GRAMACCIOLI, C. M. & MANNUCCI, G. (1988). Am. Mineral. 73, 601-607. BROWN, I. D. (1980)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…KMo 4 O 6 , for instance, crystallizes in two modifications, a highpressure polymorph in P4/mbm as well as a slightly distorted variant in Pbam stable at ambient temperature and pressure. Superstructure formation by vacancy ordering in space group Pbam was reported for Ba 0.62 Mo 4 O 6 by Torardi & McCarley (1981) or in space group P4/mnc for Pb 0.75 Mo 4 O 6 (Wang & Yeh, 1991). NMR experiments indicated that NaMo 4 O 6 itself may be incommensurately modulated and that a lowtemperature phase transition occurs at ca 140 K (Chu & Gerstein, 1989).…”
Section: Introductionmentioning
confidence: 85%
“…KMo 4 O 6 , for instance, crystallizes in two modifications, a highpressure polymorph in P4/mbm as well as a slightly distorted variant in Pbam stable at ambient temperature and pressure. Superstructure formation by vacancy ordering in space group Pbam was reported for Ba 0.62 Mo 4 O 6 by Torardi & McCarley (1981) or in space group P4/mnc for Pb 0.75 Mo 4 O 6 (Wang & Yeh, 1991). NMR experiments indicated that NaMo 4 O 6 itself may be incommensurately modulated and that a lowtemperature phase transition occurs at ca 140 K (Chu & Gerstein, 1989).…”
Section: Introductionmentioning
confidence: 85%